2013
DOI: 10.1111/jce.12166
|View full text |Cite
|
Sign up to set email alerts
|

Combined Dominant Frequency and Complex Fractionated Atrial Electrogram Ablation After Circumferential Pulmonary Vein Isolation of Atrial Fibrillation

Abstract: A combined high-DF and continuous CFAE site ablation in all chambers after circumferential PVI may be effective in the paroxysmal and persistent AF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(98 citation statements)
references
References 27 publications
3
94
1
Order By: Relevance
“…These findings have remarkably changed the management and prognostics of patients with atrial fibrillation via a new procedure of catheter ablation of atrial fibrillation that is guided by CFAE mapping [33]. Recent clinical studies of guided CFAE ablation revisited the benefits and risks of this procedure and clearly suggest that further investigation on this topic is required [3436]. Different computer simulations have also already given valuable insights into how the microstructure of cardiac tissue, specifically microfibrosis, and CFAE are related [13, 15].…”
Section: Introductionmentioning
confidence: 99%
“…These findings have remarkably changed the management and prognostics of patients with atrial fibrillation via a new procedure of catheter ablation of atrial fibrillation that is guided by CFAE mapping [33]. Recent clinical studies of guided CFAE ablation revisited the benefits and risks of this procedure and clearly suggest that further investigation on this topic is required [3436]. Different computer simulations have also already given valuable insights into how the microstructure of cardiac tissue, specifically microfibrosis, and CFAE are related [13, 15].…”
Section: Introductionmentioning
confidence: 99%
“…High-DF are also considered as a target of AF ablation and are reported to have some influence on the termination of paroxysmal AF. 8 In the present study, the sites of high-DF recorded during SR had fractionated electrograms, for example, a low voltage, long duration and high deflection, which may indicate slow conduction and wave collision in the LA. Atrial fibrosis is reported to be the result of LA remodeling and produces fractionated electrograms in the LA.…”
Section: Coa and High-frequency Sourcesmentioning
confidence: 94%
“…The high-DF cut-off was set at 8 Hz according to previous studies. 7, 8 The surface area of con-CFAE and high-DF was created by the NavX system and the total surface of those sites and the area of overlap with CoA were calculated and analyzed.…”
Section: Cfae and Df Mapping During Afmentioning
confidence: 99%
“…We used a < 0.5 mV threshold for abnormally low voltage and focused on the posterior wall since the posterior wall has been targeted for ablation in other studies and has been reported to commonly harbor regions of low voltage bipolar electro grams [6,11]. This shift was an empiric one and only 3 of our 6 operators made the change in ablation strategy.…”
Section: Af Classification and Ablation Strategy: Time For A New Paramentioning
confidence: 99%